Temporal components of cholinergic terminal to dopaminergic terminal transmission in dorsal striatum slices of mice. (22nd July 2014) - Wang, Li; Zhang, Xiaoyu; Xu, Huadong; Zhou, Li; Jiao, Ruiying; Liu, Wei; Zhu, Feipeng; Kang, Xinjiang; Liu, Bin; Teng, Sasa; Wu, Qihui; Li, Mingli; et al.
Abstract : Key points: The timing of synaptic transmission is critical to synaptic plasticity in the striatum. However, the timing of striatal dopamine (DA) release induced by cholinergic interneurons (ChIs) in the striatum is unclear. In this study, we focused on the temporal components of DA release and replenishment triggered by different pathways. We show that stimulation of ChIs induces DA release with a total delay of 20.6 ms, including 2.8 ms for action potential firing of ChIs, 7.0 ms for cholinergic transmission between acetylcholine terminals and DA terminals, and 10.8 ms for downstream DA release. The delay of DA release via this ChI pathway is 1.9 times that via the nigrostriatal pathways. We describe the time course of recovery of DA release via the two pathways and that of vesicle replenishment in DA terminals. Our work provides an example of unravelling the temporal building blocks during fundamental synaptic terminal–terminal transmission. Abstract: Striatal dopamine (DA) is critically involved in major brain functions such as motor control and deficits such as Parkinson's disease. DA is released following stimulation by two pathways: the nigrostriatal pathway and the cholinergic interneuron (ChI) pathway. The timing of synaptic transmission is critical in striatal circuits, because millisecond latency changes can reverse synaptic plasticity from long‐term potentiation to long‐term depression in a DA‐dependent manner. Here, we determined the temporal components of ChI‐driven DA release in striatal slices from optogenetic ChAT‐ChR2‐EYFP mice. After a light stimulus at room temperature, ChIs fired an action potential with a delay of 2.8 ms. The subsequent DA release mediated by nicotinic acetylcholine (ACh) receptors had a total latency of 17.8 ms, comprising 7.0 ms for cholinergic transmission and 10.8 ms for the downstream terminal DA release. Similar latencies of DA release were also found in striatal slices from wild‐type mice. The latency of ChI‐driven DA release was regulated by inhibiting the presynaptic vesicular ACh release. Moreover, we describe the time course of recovery of DA release via the two pathways and that of vesicle replenishment in DA terminals. Our work provides an example of unravelling the temporal building blocks during fundamental synaptic terminal–terminal transmission in motor regulation.